EVALUATION OF THE MATURATION TIME OF ABATTOIR-SOURCED WATER BUFFALO (Bubalus bubalis) OOCYTES FERTILIZED In vitro - ROSARIO, IVAN ISAIAS AVALOS; GUEVARA, OSCAR ENRIQUE ZARATE; KJELLAND, MICHAEL; ITURBE, LUZ TERESA ESPÍN; MANCERA, BELISARIO DOMÍNGUEZ; MORALES, MANUEL BARRIENTOS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The purpose of this study was to compare the maturation, cellular division, and blastocyst production rates of water buffalo oocytes at 18, 21 and 24 hours of incubation. These oocytes were obtained through follicular puncture, assessed, and matured in BO-IVM medium at 38.5°C, and with a 5% of CO2, at 18 (n=31), 21 (n=34) and 24 hours (n=33). Fertilization was done in a BO-IVF medium at 38.5°C, and with a 5% of CO2, for 18 hours; the maturation rate was assessed a day after fertilization. The embryos were cultured in a BO-IVC medium, at 38.5°C, 5% CO2, 7% O2 and 88% N2, and the cell division rate and number of embryos were assessed at 5 and 7 days after fertilization, respectively. The maturation rate was comparable (P>0.05) among the three groups, while blastocyst production and cell division rates were higher in the group of oocytes matured for 18 hours (P<0.05) than in the 24-hour group. The blastocyst production and cellular division rates in oocytes that were matured for 21 hours were comparable (P>0.05) to the other groups. After 21 hours of maturation, oocytes started to degenerate, which resulted in lower cellular division and blastocyst production rates.